Molecular and Immunological Mechanisms Linking EBV Infection to Multiple Sclerosis: Literature Review - Czechowski, Michał; Sikora, Gabriela; Woźniak, Martyna; Kutnik, Karolina; Koguc, Karolina; Kusibab, Karolina; Skórska, Gabriela; Słomianny, Marcela; Kolada, Karolina; Sajda, Małgorzata (Journal of Education, Health and Sport, 2025)
Background: Epstein–Barr virus (EBV), a ubiquitous herpesvirus, has been increasingly implicated as a key environmental factor in the pathogenesis of multiple sclerosis (MS). Nearly all individuals with MS are EBV-seropositive and mounting epidemiological and immunological evidence suggests a causal relationship. Objective: This review aims to summarize current knowledge on the potential mechanisms by which EBV infection contributes to MS development, with a particular focus on immunopathology, genetic susceptibility and therapeutic implications. Methods: A literature search was conducted using PubMed, Google Scholar, and ResearchGate. Key terms included “Epstein–Barr virus,” “EBV,” “multiple sclerosis,” “EBNA1,” “molecular mimicry,” “autoimmunity,” and “HLA-DRB1*15:01.” Studies published between 2005 and 2024 were reviewed, with emphasis on high-impact research articles and recent findings. Results: Several mechanisms have been proposed to explain the association between EBV and MS, including molecular mimicry between viral and CNS antigens, chronic latent infection of B cells, and the activation of autoreactive T cells in genetically predisposed individuals. The strong association with the HLA-DRB1*15:01 allele suggests a gene–environment interaction facilitating aberrant antigen presentation and loss of tolerance. Emerging therapies targeting EBV, including EBV-specific T cell immunotherapy and vaccination strategies offer promising avenues for disease modification. Conclusion: EBV likely plays a crucial role in MS pathogenesis, acting as a trigger of autoimmunity in susceptible individuals. Understanding the mechanisms of EBV-mediated immune dysregulation may enable the development of more targeted and preventive treatments for MS.